From the Desk of the Editor in Chief (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Not available   DOI: http://dx.doi.org/10.3329/jbcps.v29i4.11351   J Bangladesh Coll Phys Surg 2011; 29: 254